Association between measures of adiposity and blood pressure levels in adult Cameroonians. Issue 2 (3rd May 2021) - Dzudie, Anastase; Njedock, Nelson; Boombhi, Jerome; Ba, Hamadou; Amougou, Sylvie Ndongo; Kamdem, Felicite; Barche, Blaise; Nzali, Archange; Njomou, Armel; Ngwasiri, Calypse; Geh, Meh Martin; Azabji, Marcel; et al.
Abstract: Introduction: Several anthropometric measurements are variably recommended to assess adiposity in routine practice, with less agreement on their comparative performance. We assessed and compared the relationship of seven anthropometric measures of adiposity—waist circumference (WC), waist‐to‐height ratio (WHtR), Body Mass Index (BMI), Ponderal Index (PI), Conicity Index (C index), A Body Shape Index (ABSI), and Body Roundness Index (BRI)—with blood pressure (BP) levels and prevalent hypertension in adult Cameroonians. Methods: Data were collected as Cameroon's contribution to the global May Measurement Month 2017(MMM17) survey. Participants were nonpregnant adults, who had no BP measurement in the past year and with no prior hypertension diagnosis. Hypertension was defined as systolic BP ≥140 mm Hg and/or diastolic ≥90 mm Hg. Odds ratios (ORs) for the presence of hypertension per 1 SD increase in each adiposity metrics were estimated in separate logistic regression models. Assessment and comparison of discrimination used the area under the receiver operating characteristics curve (AUC) and nonparametric methods. Results: We included 14 424 participants (8210 [58.25%] female; 39.84 ± 14.33 years). There was a graded association between measures of adiposity and prevalent screen‐detected (newly diagnosed) hypertension, with effect sizes being mostly within the same range across measures of adiposity. AUC for hypertension prediction ranged from 0.709 with PI to 0.721 with BRI for single measures, and from 0.736 to 0.739 with combinations of measures of adiposity. Conclusion: WC, WHtR, and BRI were strongly associated with BP and better predicted prevalent hypertension, with effects enhanced with the inclusion of BMI.